A consensus statement on the use of biosimilar medicines in hematology in Australia. Issue 4 (14th April 2020) - Gregory, Gareth P.; Carrington, Christine; Cheah, Chan Y.; Hawkes, Eliza A.; Irving, Ian M.; Siderov, Jim; Opat, Stephen
Abstract: Despite their availability for over a decade, the exact nature of biosimilar medicines is still poorly understood with paucity of clear treatment guidelines for their use in clinical practice in Australia. Although hematologists have had experience with biosimilars in the setting of supportive care, with the approval of the first biosimilar rituximab in hematological malignancies, it is important to revisit this topic. To inform the use of biosimilar medicines in clinical practice, we have developed a consensus statement from an Expert Panel of Australian hematologists, oncologists, and cancer pharmacists. These recommendations address the approach to use of biosimilar products in place of the corresponding reference medicine in a number of different clinical contexts. Our recommendations are based on the premise that biosimilar medicines can be considered therapeutically equivalent to their reference brand and used in a similar way to the reference product in any approved indication. We advocate for local approaches to the provision of patient information, dispensing of the intended brand and pharmacovigilance, to be developed in consultation with local hematologists and aim to improve confidence in the appropriate use of biosimilar medicines and their expected outcomes among hematologists.